Influence of depressive symptoms on memory in transient global amnesia. Issue 1 (14th July 2015) - Noël, Audrey; Quinette, Peggy; Dayan, Jacques; de la Sayette, Vincent; Viader, Fausto; Desgranges, Béatrice; Giffard, Bénédicte; Eustache, Francis
Abstract : Introduction: Recent studies have shown that patients with transient global amnesia (TGA) experience a depressive mood during the episode. However, little evidence has been found of possible mood congruency effects on memory, which are probably masked by the massive anterograde amnesia. An implicit assessment could provide a means of settling this question. Methods: First, we measured patients' emotional states on psychopathological scales. Second, we administered a lexical decision task to assess three priming effects: Semantic priming (SP; table–chair ), emotional priming (EP; murder–garbage ), and emotional plus semantic priming (ESP; cemetery–coffin) . Results: Patients displayed a more depressed mood than controls. For patients, we found a SP effect in the ESP condition and a striking inhibition effect (i.e., negative target recognized more slowly when preceded by a negative prime rather than a neutral one) in the EP condition. For controls, a priming effect was found in the SP and ESP conditions, but not the EP condition. Finally, whereas the priming effect was greater in SP than in the other two conditions for controls, for patients it was the EP condition that stood out from the other two, being the only condition that led to an inhibition effect. Conclusions: We highlighted a mood congruency effect in TGA which could impel patients to focus their attention on negative information. While the negative valence of items always led to a slowdown in reaction times for both patients and controls, attesting to a negativity bias, this bias was greater in patients, leading to an inhibition effect.